2015
DOI: 10.1103/physrevb.92.144421
|View full text |Cite
|
Sign up to set email alerts
|

Identification of electronic state in perovskiteCaCrO3by high-pressure studies

Abstract: CaCrO 3 is at the crossover from localized to itinerant electronic behavior, and interpretation of its electronic state has remained controversial. It is a metal from an optical study. However, the collinear type-C antiferromagnetic spin ordering below T N ≈ 90 K is characteristic of localized electron magnetism. We have performed many runs of high-pressure synthesis. CaCrO 3 crystals can be found in some batches. We have used specific-heat measurement as a diagnostic tool to probe the electronic states near t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The temperature dependence of resistivity measurement results are shown in Figure 10. Although systematic changes with x are not clear, semiconductive behavior was observed for the Sr x Ca 1−x CrO 3 series samples, implying that localized electronic state in this system was consistent with the polycrystalline measurement result and the recent research on its electronic state [10,27,28]. Without the influence of surface pollution and the grain boundary effect, this result should be more accordant with its intrinsic character.…”
Section: Electrical Transport Propertiessupporting
confidence: 73%
See 2 more Smart Citations
“…The temperature dependence of resistivity measurement results are shown in Figure 10. Although systematic changes with x are not clear, semiconductive behavior was observed for the Sr x Ca 1−x CrO 3 series samples, implying that localized electronic state in this system was consistent with the polycrystalline measurement result and the recent research on its electronic state [10,27,28]. Without the influence of surface pollution and the grain boundary effect, this result should be more accordant with its intrinsic character.…”
Section: Electrical Transport Propertiessupporting
confidence: 73%
“…The sample reported here is close to the nominal composition. Zhou et al [27] measured the specific heat of a single-crystal and polycrystalline CaCrO 3 . The result indicated that the single-crystal sample with oxygen stoichiometry was insulating while the polycrystalline sample with different oxygen content was metallic [27].…”
Section: Electrical Transport Propertiesmentioning
confidence: 99%
See 1 more Smart Citation